Reasons for delay in turnover time in operating room- an observational study (Bangladesh Journal of Medical Science, 2017)
Background: Operating room (OR) like casualty room is the most productive area of a hospital. Turnover time although is a non-productive time in the operating room, yet it is important. Its efficient utilisation require multidisciplinary team work especially supporting services which play a major role in reducing turnover time in the operating room. Since present medical college where study was being conducted is still in its evolving stage, it was considered desirable for its quality improvement to study various factors which are contributing in turnover time delay so that appropriate measures can be taken to prevent the undue turnover time delay.Materials and methods: Present prospective observational case study aims at measurement of turnover time delays during 100 working days which were completed over four months for two operation theatres. The variable chosen was the delay of turnover time from the benchmark time taken. The data were collected, compiled and analysed.Results: In orthopaedics OR 77% of turnovers were found within benchmark limits. Only in 23% cases turnovers were delayed. 47% of times hospital related issues were responsible. In surgery OR 79% of turnovers were within benchmark limits. 21% cases were delayed; of this hospital related problems caused delayed turnovers in 53% cases.Conclusions: The study concluded that reasons for delays centred on multifactorial reasons which were unavoidable and unpredictable. But if those problems that can be easily fixed are attended to, valuable time can be saved, which will ultimately keep the surgeries on schedule and will prevent cancellation of elective cases. The utilization of OT complex can be optimized by team effort, multitasking and parallel processing.Bangladesh Journal of Medical Science Vol.16(2) 2017 p.245-251